Visual Function in Preterm Infants without Major Retinopathy of Prematurity or Neurological Complications - Kozeis, Nicolaos; Mavromichali, Maria; Soubasi-Griva, Vasiliki; Agakidou, Eleni; Zafiriou, Dimitris; Drossou, Vasiliki (American Journal of Perinatology, 2012)
Objective Early exposure of preterm infants to visual stimulation could affect the process of visual maturation. The aim of this study was to assess the impact of prematurity on visual function at 15 months post-term.Subjects and Methods Visual function was assessed in 102 preterm (PTI) and 50 full-term infants (FTI) without major cerebral pathology or retinopathy of prematurity (ROP) of grade 2 to 5, at 15 months' corrected age. The visual acuity, refractive status, contrast sensitivity, strabismus, fundus, and neurodevelopment were examined.Results Impairments of individual visual functions were 2 to 10 times more common in PTI than FTI. However, the difference was significant only for refractive errors (p = 0.007, odds ratio [OR] = 10.5). The incidence of visual deficits was higher in PTI with gestational age less than 32 weeks compared with PTI with higher gestational age (OR = 1.3 to 2.0), but not significantly. Of the PTI, 4.9%, 2.9%, and 10.8% had mild abnormalities on ultrasound scans, neuromotor, and developmental examination, respectively, which were not associated with increased incidence of visual deficits.Conclusion Premature exposure to visual stimulation does not induce visual maturation but it is associated with impairment of certain aspects of visual function even in the absence of major ROP or neurodevelopmental deficits.
Keywords: contrast sensitivity; prematurity; refractive errors; strabismus; vision; visual acuity